Activities on Numeracy Skills and Independence in Deep Learning with Interactive Teaching Materials in Elementary Schools - Indah Setyaningsih; Achmad Buchori; Joko Sulianto (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
The delivery of material using less varied methods, namely lectures and assignments, causes students' low mathematical abilities. This study aims to analyze the effect of student activity on numeracy skills and learning independence through an in-depth learning approach assisted by interactive teaching materials in schools. The type of research used is a quasi-experimental research (quasi-experimental) using a quantitative approach. The sampling technique used was purposive sampling, with a total of 25 students in the experimental class and 25 students in the control class. Data collection methods used in this study were tests, questionnaires, and observations. The research instruments were in the form of test questions and questionnaires. Data analysis techniques used inferential statistics. The research findings show that student activity significantly affects numeracy skills and learning independence. The post-test results showed a significant increase after the implementation of in-depth learning with interactive teaching materials. The results of the N-Gain test placed the effectiveness of in-depth learning with interactive teaching materials in the moderate category, with an average score of 0.6147 (61.47%). Scores ranged from 0.33 to 1.00, reflecting diverse student responses influenced by prior abilities, motivation, and adaptability to technology. This study concluded that the model was effective in improving conceptual understanding, student engagement, and learning independence. This study implies that an immersive learning approach supported by interactive learning materials can be used to improve numeracy skills and learning independence in students.